Bacterial contamination and nutritional adequacy of enteral tube feedings in Iran - Mahinkazemi, Mahsa; Tarighat-Esfanjani, Ali; Safaiyan, Abdolrasoul (Progress in Nutrition, 2017)
Background: In spite of recent advances in nutritional support, researches are often unclear and, in many cases, conflicting in regard to the most appropriate formulas. This study aimed to evaluate nutritional adequacy and bacterial contaminations of enteral feedings (EFs) that are used in the intensive care units (ICUs) of hospitals in Tabriz, Iran. Methods: This experimental study was carried out on 54 EFs samples; 36 blenderized tube feedings (BTFs) and 18 commercial powder feedings (CPFs) of patients in the ICUs. Energy and macronutrients contents of formulas were measured and compared with estimated needs of patients. Thirty-six BTFs samples (18 after preparation and 18 after 18 hour keeping in refrigerator) and 18 CPFs samples immediately after preparation were tested for the presence of total coliforms, Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Listeria monocytogenes (L. monocytogenes), and Salmonella. Results: The energy density (ED) of BTFs (0.74±0.02 kcal/mL) were higher than CPFs (0.59±0.02 kcal/mL) and both lower than predicted values (p